Survival outcomes and prognostic factors in children and adults with medulloblastoma from a Latin America country: A retrospective cohort - Michael Mallouh; Gabriel De la Cruz-Ku; Renato Luque-Benavides; Bryan Valcarcel; Flavia Rioja; Martin Hemeryth; J. Smith Torres-Roman; Diego Chambergo-Michilot; Juan Haro Varas; Daniel Enriquez-Vera; Jhajaira M. Araujo; Rosdali Diaz-Coronado; et al. (PLoS ONE, 2025)
Background Few studies have evaluated the real-world outcomes of patients with medulloblastoma with contradictory results. Therefore, we aimed to compare the characteristics, survival outcomes, and prognostic factors between children and adults with medulloblastoma. Methods We conducted a retrospective cohort study in a single academic center between 2000 and 2016. Patients were categorized into children and adolescents (≤19 years) and adults (>19 years). Overall survival (OS) and disease-free survival (DFS) were estimated with the Kaplan-Meier method. Prognostic factors were determined using Cox models. Results In total, 173 patients were included (79 adults and 94 children). No differences were observed in clinical characteristics according to age groups. At 5 years, DFS was 36.88% in children and 50.99% in adults (p = 0.476). Prognostic factors of DFS in adults were radiotherapy (adjusted Hazard ratio [aHR]: 0.22; 95% confidence interval [CI]: 0.07–0.67) and performance status 2–4 (aHR: 3.60; 95% CI: 1.48–8.77); while in children was radiotherapy (aHR: 0.33; 95% CI: 0.11–0.96) and chemotherapy (aHR: 0.34; 95% CI: 0.14–0.84). The 5-year OS rate was 64.25% in children and 60.87% in adults (p = 0.447). In adults, prognostic factors of OS were histologic type (aHR: 6.11, 95% CI: 1.19–31.48, for anaplastic) and radiotherapy (aHR: 0.22, 95% CI: 0.07–0.71), while in children and adolescents, lower performance status (aHR: 2.43, 95% CI: 1.09–5.39, for performance status 2–4) was the only prognostic factor. Subgroup analyses revealed a trend toward improved DFS and significantly better OS among adults who completed chemotherapy, highlighting the importance of treatment adherence. Conclusions Both populations demonstrated similar survival rates that were comparable to or lower than those reported in previous studies. In adults, performance status and radiotherapy were prognostic factors for DFS, while histologic type and radiotherapy for OS. In children, chemotherapy and radiotherapy were prognostic factors for DFS, and performance status was the only OS prognostic factor. These findings underscore the importance of optimizing treatment adherence and completing standard therapies, as well as improving staging practices, to enhance outcomes in real-world settings.